Testing of Shoreline Erosion Monitoring Methodologies for Heritage at Risk Sites: Pockoy Island, South Carolina, USA. - Gaillard, Meg; Luciano, Katie; Sundin, Gary; Weber, Kiersten; Smith, Karen Y. (Advances in Archaeological Practice, 2024)
We review shoreline monitoring methodologies used by members of the South Carolina Department of Natural Resources (SCDNR) Archaeology, Geology, and Wildlife Biology teams from February 2021 to December 2022 on Pockoy Island in Charleston County, South Carolina, USA. Our project objectives were to better understand the driving forces behind the landward movement of the shoreline (transgression), to apply new understanding to the rate of shoreline erosion of the island that directly impacts the Pockoy Island Shell Ring Complex (38CH2533), and to establish best practice for future community science monitoring efforts. Each member of our team used a different shoreline monitoring methodology (a nested methodology approach). Multiple unoccupied aerial vehicle (UAV)-derived orthoimagery datasets, on-the-ground transect measurements, and Arrow Gold real-time kinematic (RTK) unit measurements have been collected monthly following significant storms or king (perigean) tide events. Moving forward, the erosion transect approach tested within this project will serve as the foundation for community science monitoring at heritage at-risk sites in South Carolina. In this article, we introduce initial efforts in establishing a community science monitoring program in South Carolina that will influence future research, land management, and policy, and we propose how our research might be adapted for other sites at risk.